PENGABDIAN KEPADA MASYARAKAT MELALUI KEGIATAN MBKM DI KSP CREDIT UNION KELUARGA KUDUS TEMPAT PELAYANAN BENGKAYANG - Noviyani, Aprilia; Salfarini, Eligia Monixa (Jurnal Pengabdian Bukit Pengharapan, 2024)
Community service through MBKM activities at the Holy Family Credit Union Savings and Loans Cooperative has a positive impact on internship students, where students learn a lot and gain experience in the world of work, students provide assistance to administrative and general staff, where students assist admin staff in working and completing reports relating to customers or members of Holy Family Credit Union. While carrying out this internship, students also apply the 3S culture (Smile, Greet and Greeting). Students apply it at the cashier when they are given the task of looking after the cashier, in the internalization room in the morning and in the kitchen during break times and eating together. This internship location is very suitable for ShantiBhuana Institute students because the Holy Family Credit Union Savings and Loans Cooperative has values ​​that are applied, one of which is Trust or trust, which values ​​are also applied at the ShantiBhuana Institute. At the internship site, students meet many new people who are members of the Holy Family Credit Union who carry out savings activities or make loans. The 3S culture really needs to be implemented in the internship location, namely at the Holy Family Credit Union because with the 3S culture, members will feel comfortable with the services at the Holy Family Credit Union and the relationship between members and staff will feel increasingly warm, like family. This internship activity also really helps students to hone their skills in the world of work and students also gain new relationships which will be very useful when students have completed their studies at the ShantiBhuana Institute and will then start entering the world of work.